Peru Opportunities and Challenges of Small Hydropower Development - Meier, Peter; Zolezzi, Eduardo H.; Bogach, Susan V.; Muir, Terence; Bazex, Karen (World Bank, Washington, DC, 2014)
Peru is favored by a stable and growing economy and the availability of indigenous sources of energy for electricity generation, including hydro and natural gas. The Peruvian electricity sector is among the few in Latin America and Caribbean (LAC) that has not confronted a crisis in recent years. The power sector in Peru was reformed and restructured between 1991 and 1993, followed by a privatization and concession process. A modern legal and regulatory framework was established in the electricity concessions law of 1992-93. This report contains the following chapters: (1) introduction; (2) resource potential and technical capacity for development of small hydropower in Peru; (3) economic and financial viability of small hydro development in Peru; (4) institutional and regulatory environment; (5) identification of barriers to small hydropower development and mitigation measures; (6) international experience with small hydropower development; and finally (7) conclusions and recommendations.